2020
DOI: 10.3389/fmicb.2020.01416
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Animal Waste Resistome: The Spread of Antimicrobial Resistance Genes Through the Use of Livestock Manure

Abstract: Antibiotic resistance is a public health problem of growing concern. Animal manure application to soil is considered to be a main cause of the propagation and dissemination of antibiotic residues, antibiotic-resistant bacteria (ARB), and antibiotic resistance genes (ARGs) in the soil-water system. In recent decades, studies on the impact of antibioticcontaminated manure on soil microbiomes have increased exponentially, in particular for taxonomical diversity and ARGs' diffusion. Antibiotic resistance genes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 107 publications
(133 reference statements)
2
67
0
Order By: Relevance
“…Following population expansion, such bacteria may be released from the animals and reach and contaminate nearby rivers. Conventional livestock waste treatment processes cannot completely remove antibiotic-resistance genes, and result in contamination of water environments [ 52 , 53 ]. Some studies have reported the transmission of antimicrobial-resistant bacteria from pig manure to the environment [ 54 ], and these antibiotic-resistant bacteria may spread through water [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following population expansion, such bacteria may be released from the animals and reach and contaminate nearby rivers. Conventional livestock waste treatment processes cannot completely remove antibiotic-resistance genes, and result in contamination of water environments [ 52 , 53 ]. Some studies have reported the transmission of antimicrobial-resistant bacteria from pig manure to the environment [ 54 ], and these antibiotic-resistant bacteria may spread through water [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting because we might expect the selective pressures in the mammalian gut that enrich ARGs to be decreased in environmental settings. Lack of ARG depletion suggests that either ARGs are maintained outside the gut, possibly by stable plasmids or by selective pressures from the excreted antimicrobials that are not metabolized, or ARGs are introduced to the manure pits from sources other than the dairy cow gut (18,30,32). Further, we found a reconfiguration in the composition of ARGs, with specific ARGs being enriched in either fresh manure or manure pits and an increase in beta diversity between fresh manure and manure pits.…”
Section: Discussionmentioning
confidence: 78%
“…However, the introduction of microbiota from the guts of animals may have adverse effects on the microbial composition and functional resistance profiles found in the environment. Past studies suggest that antimicrobial resistance may remain on farms through the acquisition of multidrug resistance and horizontal gene transfer, but it is unclear how much antimicrobial resistance spreads to fields and how that spread influences microbial composition and the total amount and diversity of functional ARGs, known as the resistome of manure and soil (30)(31)(32). Further, most studies focus on known or individual antimicrobial resistance genes of interest, missing less characterized antimicrobial genes that may be of equal concern (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Importantly, the risk of the emergence and rapid spread of livestock pathogens (such as the ASF virus) that are a threat to food security is non-existent in the case of cultured meat. Secondly, the production of cultured meat would decrease the excessive use of antibiotics that promote the emergence and spread of antibiotic-resistant bacteria ( Checcucci et al, 2020 ; He et al, 2020 ). Thirdly, the production process is much more predictable and less time-consuming with several weeks needed for the conversion of nutrients and energy instead of the months or years needed in the case of meat originating from livestock ( Bhat et al, 2015 ).…”
Section: Changes To Meat Productionmentioning
confidence: 99%